Pengaruh Implementasi Konsep Just-in-Time terhadap Efisiensi Operasional dan Pengendalian Biaya di Perusahaan Manufaktur (Studi Kasus PT Waskita Karya Tbk) - Putri Silvia Istiqomah; Wanda Vidya Nandita; Nabila Putri Sayekti (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This study aims to investigate the effect of Just-in-Time concept implementation on operational efficiency and cost control at PT Waskita Karya Tbk, a manufacturing company in Indonesia. The research population consists of purchasing employees, PCD employees, Logistics Leaders, Line Heads, Group Heads, and Section Heads. The research sample was taken saturated, with a total sample size of 24 people. The data analysis methods used include descriptive statistics and multiple regression analysis. The results showed that there was a significant regression coefficient and a p-value lower than the significance level of 0.05 (with a p-value of 0.001). This indicates that the implementation of the Just-in-Time concept has a positive and significant influence on operational efficiency and cost control at PT Waskita Karya Tbk. In addition, the relatively high R-Squared (0.718) indicates that the Just-in-Time Concept variable is able to explain about 71.8% of the variation in operational efficiency and cost control in the company. This research has novelty in the context of the application of Just-in-Time concept in the construction industry through a case study on PT Waskita Karya Tbk. The implication of this study is that the implementation of Just-in-Time concept can improve operational efficiency and cost control in manufacturing companies. The findings provide a foundation for other manufacturing companies to adopt and implement the Just-in-Time concept to improve their operational performance.